Role of ultrasound in the evaluation of thenar muscles length - Sidek, Sabrilhakim; Mohd Khalid, Mohd Shukry; Roslan, Rozaidi; Sidek, Shahrul Na'im (2016)
Proper functioning of the hand is centered on the use of the thumb, which is the only opposable finger among the five. Assessment of the thenar muscles that is essential for thumb movement is important in not only medical field as to look for any pathology, but also crucial in the engineering field. Assessment of these muscles can be applied to develop a prostatic thumb which can mimics the real actions of a real thumb as closely possible. Muscle length is one of the parameters needed to develop a prostatic thumb. Therefore, in this study, we utilized ultrasound technique to measure thenar muscles length and the precision of this technique is compared with the MRI examination as gold standards